Environmental Hazards and Neurodevelopment 2015
DOI: 10.1201/b18030-15
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF INFANTILE MINERAL IMBALANCES IN AUTISM SPECTRUM DISORDERS (ASDs)

Abstract: The interactions between genes and the environment are now regarded as the most probable explanation for autism. In this review, we summarize the results of a metallomics study in which scalp hair concentrations of 26 trace elements were examined for 1,967 autistic children (1,553 males and 414 females aged 0-15 years-old), and discuss recent advances in our understanding of epigenetic roles of infantile mineral imbalances in the pathogenesis of autism. In the 1,967 subjects, 584 (29.7%) and 347 (17.6%) were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
2
12
1
1
Order By: Relevance
“…It comprised 40 children diagnosed as ADHD according to the diagnostic and statistical manual of mental disorder (DSM-5) criteria [18] by psychiatrist. They were recruited from psychiatric outpatient clinic at Alzahraa University hospital.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It comprised 40 children diagnosed as ADHD according to the diagnostic and statistical manual of mental disorder (DSM-5) criteria [18] by psychiatrist. They were recruited from psychiatric outpatient clinic at Alzahraa University hospital.…”
Section: Methodsmentioning
confidence: 99%
“…OP pesticides exposure during growing might have constant effects on multiple neural systems that lead to ADHD behaviors, such as inattention and cognitive deficits, which is similar to the symptoms due to nicotine exposure during development [14,15]. Globally ADHD is considered one of the main prevalent neurobehavioral disorders in children, affecting three to ten percent of children [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are particularly prominent in terms of nonfatal burden, accounting for 0.8% of the years lived with disability across all ages [151]. Attention deficit hyperactivity disorder is diagnosed in mid-childhood and the prevalence declines with age, being 5-10% in childhood, 2.5-4% in adolescents and 2.5% in adults [152,153]. A recent pooled analysis suggested a global prevalence of 5.3% for attention deficit hyperactivity disorder in children and adolescents, although parental reports of symptoms consistent with attention deficit hyperactivity disorder often give higher estimates, with 7.2% of American children 4-17 years of age reported by parents to have a current diagnosis of attention deficit hyperactivity disorder [154].…”
Section: Neurocognitive Disordersmentioning
confidence: 99%
“…AGUIAR et al [152] reported that the most common comorbidities in boys are oppositional defiant disorder (>32%) and conduct disorders (>7%), while anxiety disorders (33%) are more common in girls, and depression and bipolar disorders are common in adolescents. There is less certainty over whether attention deficit hyperactivity disorder is associated with decreased cognitive function and lower intelligence quotient (IQ), although several of the environmental exposures associated with attention deficit hyperactivity disorder (see later), including lead [155], polychlorinated biphenyls [155], organochlorine pesticides [155], organophosphate pesticides and tobacco smoke [156], are associated with lower IQ.…”
Section: Neurocognitive Disordersmentioning
confidence: 99%